问题
解答题
计算 (1)-42-6×
(2)[(-1
(3)化简:-4(a3-3b)+(-2b2+5a3) (4)化简求值:-2x2-
(5)解方程:3(x-1)-5(3-2x)=8(x-8)+6;
|
答案
(1)原式=-16-8-2×(-2)
=-16-8+4
=-20;
(2)原式=[(-
)+(-16 9
)+17 6
]×(-36)47 12
=(-
)×(-36)+(-16 9
)×(-36)+17 6
×(-36)47 12
=64+102-141
=25;
(3)原式=-4a3+12b-2b2+5a3
=(-4+5)a3-2b2+12b
=a3-2b2+12b;
(4)原式=-2x2-
[5y2-2x2+6],1 6
=-2x2-
y2+5 6
x2-11 3
=-
x2-5 3
y2-1,5 6
当x=-2,y=-0.5时,原式=(-
)×4-5 3
×5 6
-11 4
=-
-20 3
-15 24
=-
;63 8
(5)3(x-1)-5(3-2x)=8(x-8)+6,
去括号得,3x-3-15+10x=8x-64+6,
移项得,3x+10x-8x=-64+6+3+15,
合并同类项得,5x=-40,
系数化为1得,x=8.
解方程:
[x+1 2
(1-x)]=1 3
(x+1),2 3
去分母得,3x+(1-x)=4(x+1),
去括号得,3x+1-x=4x+4,
移项得,3x-x-4x=4-1,
合并同类项得,-2x=3,
系数化为1得,x=-
.3 2